Role of Credit and Technology in Income and Employment Generation in Paddy Farms of Tanjong Karang and Beranang, Malaysia - Yadav, Devendra Prasad (1990)
The paddy sub-sector assumes an important position in Malaysian agriculture. It is characterized by a high level of poverty of 50.2 per cent in 1987, and a range of structural problems including low productivity, high product ion cost and short age of labour. Technologically movativation is seen to be important in overcoming these problems. The fact that paddy production is now confined only to the granary areas means that technology will become increasingly important as a means to increase productivity and output if the target ted 60-75 percent national self sufficiency level is to be attained. This study aims to elucidate the role and impact of credit on technology and farm performance among paddy farmers. Two samples of paddy farmers are chosen, one from Tanjong Karang which represents a technologically advanced area, and the other from Beranang which re presents atraditional and less innovative area.